Synergistic Excitation Mechanism of CaO-SiO2-Al2O3-SO3 Quaternary Active Cementitious System - Niu, Fusheng; An, Yukun; Zhang, Jinxia; Chen, Wen; He, Shengtao (Frontiers in Materials, 2021)
In this study, the influence of steel slag (SS) content on the strength of the cementitious materials was investigated. The quaternary active cementitious material (CaO-SiO2-Al2O3-SO3) was prepared using various proportions of steel slag (SS), granulated blast furnace slag (BFS), and desulfurized gypsum (DG). The mechanism of synergistic excitation hydration of the cementitious materials was examined using various techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectrometry (FTIR). The strength of the mortar test block was initially increased and decreased later with the increase of the SS content. Mortar test block with 20% steel slag, 65% granulated blast furnace slag, and 15 % desulfurized gypsum with 0.35 water-binder ratio showed the highest compressive strength of 57.3MPa on 28 days. The free calcium oxide (f-CaO) in the SS reacted with water and produced calcium hydroxide (Ca(OH)2) which created an alkaline environment. Under the alkaline environment, the alkali-activated reaction occurred with BFS. In the early stage of hydration reaction, calcium silicate hydrate (C-S-H) gel and fibrous hydration product ettringite (AFt) crystals were formed, which provided early strength to the cementitious materials. As the hydration reaction progressed, the interlocked growth of C-S-H gel and AFt crystals continued and promoted the increase of the strength of the cementitious system.